Model Belajar Synchronous dan Ansynchronous Dalam Menghadapi Learning Loss - Moch. Mahsun; Taqwa Nur Ibad; Alfi Nurissurur (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
The restrictions on educational activities were felt by Indonesia because of the Covid-19 pandemic and caused learning loss or failure of understanding in students, forcing the government to open schools again using a synchronous learning model, namely direct face-to-face learning and face-to-face indirect learning called ansynchronous. This research is a case study research that uses qualitative methods, the research object is Lumajang secondary education, the data obtained from observations, interviews and documentation are then analyzed using the triangulation analysis method. The learning model of MAN Lumajang uses a synchronous learning model using the E-Learning application, it's just that it is not optimal so that the impact such as learning loss is still very pronounced with the division of classes twice a week face to face. Meanwhile, SMAN 1 Lumajang uses a synchronous learning model using the MT (Microsoft Team) application, but it is not optimal, so the impact such as learning loss is still felt by dividing classes twice a week face to face. SMKN 1 Lumajang uses an asynchronous learning model using the Google Classroom application, its use is maximized so that the impact such as learning loss is still not felt by dividing classes once a week face to face.